2012
DOI: 10.1261/rna.034926.112
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-182-5p targets a network of genes involved in DNA repair

Abstract: MicroRNAs are noncoding regulators of gene expression, which act by repressing protein translation and/or degrading mRNA. Many have been shown to drive tumorigenesis in cancer, but functional studies to understand their mode of action are typically limited to single-target genes. In this study, we use synthetic biotinylated miRNA to pull down endogenous targets of miR-182-5p. We identified more than 1000 genes as potential targets of miR-182-5p, most of which have a known function in pathways underlying tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 73 publications
7
91
0
4
Order By: Relevance
“…Medimegh et al have noticed a significant association of lymph node metastases with miR-182 overexpression in TNBC of Tunisian population [19]. In present study we did not find any significant association between miR-182-5p expression and lymph node status, which is consistent with results of Krishnan et al (2013) [24].…”
Section: Discussionsupporting
confidence: 91%
“…Medimegh et al have noticed a significant association of lymph node metastases with miR-182 overexpression in TNBC of Tunisian population [19]. In present study we did not find any significant association between miR-182-5p expression and lymph node status, which is consistent with results of Krishnan et al (2013) [24].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, overexpression of an exogenous miRNA (even at the low levels used in this study) could also lead to competition for gene targets with endogenous miRNAs, leading to false positives in our assay. Although we do not observe major disruption to the transcriptional landscape either here or in previous studies (Cloonan et al 2011;Krishnan et al 2013), this potential requires that studies of individual miRNA targets will need to be individually validated (Fig. 6).…”
Section: Discussionmentioning
confidence: 49%
“…For instance, miR-17-5p is oncogenic in hepatocellular and colorectal carcinomas (Ma et al 2012;Shan et al 2013) and, in contrast, has been shown to have tumor-suppressive properties in cervical cancer cells . Similarly, miR-182-5p was shown to have oncogenic properties in bladder, ovarian, and breast cancers (Hirata et al 2012;Liu et al 2012;Krishnan et al 2013), whereas it acts as a tumor suppressor in lung cancer . Given this molecular and context specificity of miRNAs, we wished to explore whether miR-139-5p was a potential oncomir of breast cancer and what the output of its functional repression was, and identify the network of genes possibly regulating its functions in the context of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The miR-182-5p is considered to have dual properties as an oncogene and tumor suppressor depending on the cellular context. It targets many genes positively regulating DDR but also cyclin-dependent kinase 6 (CDK6), which phosphorylates retinoblastoma 1 protein (RB1) and consequently promotes cell cycle progression (74). Both miRNAs were up-regulated at the latest 24 h time point and we could not detect any differences between healthy controls and the AT.…”
Section: Figmentioning
confidence: 66%